Translation Techniques as a Message for Target Readers in Children Story ‘Widget’ - Nunun Tri Widarwati; Purwani Indri Astuti; Arin Arianti; Giyatmi Giyatmi (Scope : Journal of English Language Teaching, 2021)
In the case of translating children stories, translators need to be an extra careful since children stories are not just about fun, but children stories usually also contain moral messages. Different from translating texts for adults, the role of translators as a filter in translating children text is greater since unlike adult, children ability to do self-filter in absorbing any material they read is very weak. Therefore, translating this kind of text is certainly a challenge for translators: on one side they have to deliver the message, and on another they have to make sure that their translation should still deliver moral message to target readers. This research captures the effort of translators in trying to do both through their choice of translation techniques in translating children story Widget. The goal of the research is to investigate and to explain the translation techniques used by translators in translating Widget. The research employed qualitative analysis with the data in the form of sentences in the story with total sampling. The results of the research show that various translation techniques are chosen to deliver the message of the original text in the translation such as established equivalent, pure borrowing, explicitation, transposition, compensation, modulation, and reduction. In addition to that, some of them were chosen especially in order to deliver the target readers in terms of the culture of original text.